Early maladaptive schemas and depression in hospitalized young patients - Meza Arroyo, Karla Ivette (2019)
This research is quantitative, with a descriptive and correlational design. Its objective is to compare the relationship between the early maladaptive schemas and the depression developed in hospitalized young patients from a Healthcare Institution in Lima. The sample consisted of 100 male patients ranging from 18 and 23 years old, admitted to different hospital units. The outcome yielded that the only early maladaptive schema related to depression is the negativity schema with a 95% confidence interval. Therefore, it is concluded that the unmet needs of these individuals are spontaneity and play as their feelings, impulse and choices were repressed during childhood, thus causing a pessimistic outlook in adulthood.